2017
DOI: 10.1021/acs.jpcb.6b11279
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Mean Force Calculations of Solute Permeation Across UT-B and AQP1: A Comparison between Molecular Dynamics and 3D-RISM

Abstract: Membrane channels facilitate the efficient and selective flux of various solutes across biological membranes. A common approach to investigate the selectivity of a channel has been the calculation of potentials of mean force (PMFs) for solute permeation across the pore. PMFs have been frequently computed from molecular dynamics (MD) simulations, yet the three-dimensional reference interaction site model (3D-RISM) has been suggested as a computationally efficient alternative to MD. Whether the two methods yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 117 publications
1
13
0
Order By: Relevance
“… 399 A comparison of UT-B and Aqp1 revealed that despite their different folds, the pore constriction radius in both pores was <0.2 nm, presenting a central energetic barrier to water in UT-B of ∼10 kJ/mol. 398 …”
Section: Aquaporins and Related Water And Polar Solute Poresmentioning
confidence: 99%
“… 399 A comparison of UT-B and Aqp1 revealed that despite their different folds, the pore constriction radius in both pores was <0.2 nm, presenting a central energetic barrier to water in UT-B of ∼10 kJ/mol. 398 …”
Section: Aquaporins and Related Water And Polar Solute Poresmentioning
confidence: 99%
“…Among other reports of biomolecular simulations using the 3D-RISM-KH theory, the effect of (micro-) solvent environments on amyloid structure and potential of mean force calculations of solute permeation across UT-B and AQP1 proteins provided further extension of the applications of the 3D-RISM-KH theory based molecular solvation [ 86 , 87 ].…”
Section: Binding Site Mappingmentioning
confidence: 99%
“…The 3-Dimensional Reference Interaction-Site Model (3D-RISM) was presented as a fast and accurate method for computing PMFs for the permeation of different solutes across aquaporin channels by Phongphanphanee et al (2010) [99]. However, we compared the PMFs calculated with 3D-RISM to the PMFs calculated with Molecular Dynamics (MD) coupled with Umbrella Sampling (US), which is a widely and commonly used computational method to calculate PMFs, and concluded that 3D-RISM is not suitable to compute PMFs of solute permeation across protein channels [65].…”
Section: Non-functional Mutants Offer Clues About the Permeation Mech...mentioning
confidence: 94%
“…In the crystal, selenourea is bound to S i and S o sites, for which independent computational studies revealed two free energy minima in the Potential of Mean Force (PMF). These urea binding sites are found at both sides of the S m region, in which a free energy maximum is observed [64,65]. Across this selectivity filter, urea permeates by establishing hydrogen bonds along the oxygen ladder without causing much perturbation to the channel (Figure 2.2).…”
Section: S M H-bond Pattern Is Crucial In the Urea Permeation Mechanismmentioning
confidence: 99%